2020
DOI: 10.1007/s00394-020-02302-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low-dose milk protein supplementation following low-to-moderate intensity exercise training on muscle mass in healthy older adults: a randomized placebo-controlled trial

Abstract: Purpose The purpose of this study was to examine whether long-term ingestion of low-dose milk protein supplementation causes a greater increase in muscle mass and strength of older adults during low-to-moderate intensity exercise training intervention than isocaloric carbohydrate. Methods In a randomized, double-blind, and placebo-controlled design, 122 healthy older adults (60–84 year) received either an acidified milk protein drink containing 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 54 publications
0
28
0
Order By: Relevance
“…However, it is relevant to highlight that the study of Nakayama et al ., 76 was the main contributor to this result according to our sensitivity analysis. Probably, because the study sample in Nakayama et al 76 . is relatively large ( n = 122) when compared with other studies in the subgroup analysis.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…However, it is relevant to highlight that the study of Nakayama et al ., 76 was the main contributor to this result according to our sensitivity analysis. Probably, because the study sample in Nakayama et al 76 . is relatively large ( n = 122) when compared with other studies in the subgroup analysis.…”
Section: Discussionmentioning
confidence: 71%
“…Sixty‐six out of 74 studies were included in the lean body mass change analysis, utilizing 2665 subjects 33–99 . Six studies presented intervention groups not using RE training 41,46,94,97–99 ; of these, four studies tested protein ingestion exclusively, 41,97–99 and two studies tested protein ingestion in groups without and with resistance exercise 46,94 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we observed the consumptions of higher amounts of protein, iodine, polyunsaturated fatty acids (PUFA), Vit E and manganese are favourable for maintenance of muscle level above the pre-sarcopenic threshold using SMM r . It is possible that food types may underlie the lower nutrient intake, where the high SMM r group had a diet richer in fish, milk, nuts and seeds, considered a high diet quality [ 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. The association of higher dietary intake of protein with better muscle phenotypes in the present study could be explained by the reported positive link between dietary protein intake and muscle protein synthesis [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the included studies, two studies provided an appropriate amount of protein (10 g milk protein and 0.5 g/kg whey protein) three times a day, taking into account frequency and distribution [21,25,26]. Other studies provided 10.1 g-25 g protein once a day [44][45][46][47] or 20 g ~ 35 g protein 3 times a week on the days exercise was performed [48][49][50]. A previous review showed that multi-ingredient protein supplements have the potential to increase the bene ts of resistance training, but there were no differences in the effects on muscle mass and strength between multi-ingredient protein and single protein [51].…”
Section: Discussionmentioning
confidence: 99%